Pengaruh Investasi dan Sumber Daya Manusia Terhadap Pendapatan Asli Daerah Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening (Studi Kasus Pada Kabupaten/Kota di Provinsi Jawa Tengah) - Anggraini, Nova; , Dr. Zulfikar, SE, M.Si (2017)
The purposes of this research are to determine the influences of Investment and human resources to local revenues through economic growth of Central Java Province. This research uses quantitative method with secondary data. Population of this research is district/city in the central java province. The research applies panel data analysis, data in19 regency/municipality and time series data for periods 2013-2014. Methods of data using path analysis model.Analysis tool uses validity, reliability, normality, multicolinierity, heteroscedasticity, regression linier, F, t, and coefficient determination test. The data obtained are then analyzed using SPSS 21.00. The result this research that there was independent variable have statistically positive and significant influence on the economic growth and local revenue in Central Java Province.